Introduction to the density matrix renormalization group ansatz in quantum chemistry - Chan, Garnet Kin-Lic; Dorando, Jonathan J.; Ghosh, Debashree; Hachmann, Johannes; Neuscamman, Eric; Wang, Haitao; Yanai, Takeshi (Frontiers in Quantum Systems in Chemistry and Physics, 2008)
The Density Matrix Renormalisation Group (DMRG) is an electronic structure method that has recently been applied to ab-initio quantum chemistry. Even at this early stage, it has enabled the solution of many problems that would previously have been intractable with any other method, in particular, multireference problems with very large active spaces. Historically, the DMRG was not originally formulated from a wavefunction perspective, but rather in a Renormalisation Group (RG) language. However, it is now realised that a wavefunction view of the DMRG provides a more convenient, and in some cases more powerful, paradigm. Here we provide an expository introduction to the DMRG ansatz in the context of quantum chemistry.

Ionization-induced tautomerization in cytosine and effect of solvation - Das, Tamal; Ghosh, Debashree (Journal of Physical Chemistry A, 2014)
The recent observation of excitation-induced tautomerization in gas-phase cytosine motivated us to investigate the possibility of facile tautomerization in ionized cytosine and the effect of solvation on the tautomerization barriers. The tautomerization mechanisms were characterized at the density functional theory (DFT)omega B97X-D and coupled-cluster singles and doubles (CCSD) levels of theory. Vertical and adiabatic ionization energies (VIEs and AIEs, respectively) of the tautomers of cytosine and the microsolvated species were calculated with the equation-of-motion ionization-potential coupled-cluster (EOM-IP-CCSD) method. We observed that, in microsolvated cytosine, the solvatochromic shifts of the VIEs can be both blue- and red-shifted depending on the tautomers. This is explained by the analysis of the charge dipole interactions between the cytosine and water molecules. We noticed that, upon ionization, gas-phase tautomerization barriers are reduced by 0-4 kcal/mol, whereas microsolvated (with one water) tautomerization barriers are reduced by 4-5 kcal/mol. We also investigated the tautomerization process in solvation using a continuum model with one active water molecule in the quantum mechanical region. We noticed that, even though bulk solvation has a significant effect on ionization energies, its effect on the ionization-induced tautomerization barrier is minimal.

Interaction energy driven biased sampling technique: a faster route to ionization spectra in condensed phase - Bose, Samik; Ghosh, Debashree (Journal of Computational Chemistry, 2017)
We introduce a computationally efficient approach for calculating spectroscopic properties, such as ionization energies (IEs) in the condensed phase. Discrete quantum mechanical/molecular mechanical (QM/MM) approaches for spectroscopic properties in a dynamic system, such as aqueous solution, need a large sample space to obtain converged estimates, especially for the cases where particle (electron) number is not conserved, such as IEs or electron affinities (EAs). We devise a biased sampling technique based on an approximate estimate of interaction energy between the solute and solvent, that accelerates the convergence and therefore, reduces the computational cost significantly. The approximate interaction energy also provides a good measure of the spectral width of the chromophores in the condensed phase. This technique has been tested and benchmarked for (i) phenol, (ii) HBDI anion (hydroxybenzylidene dimethyl imidazolinone), and (iii) thymine in water. (c) 2017 Wiley Periodicals, Inc.